Vozes femininas contra o “legado” da ditadura: mulheres e militância política no documentário brasileiro contemporâneo - Sousa, Liliane Cristina Soares (2020)
Based on a historical and historiographic analysis of the civil-military dictatorship in Brazil (1964-1985), especially after it “passed”, it analyzed or led women in resistance movements and struggles against the nefarious regime and investigates a left-wing female militancy from the spaces occupied by these women in this historical context and without a democratic transition process in the country. From the memories of women who are not in the military period and women who are fighting at the moment; being them, relatives of political dead and disappeared, ex-militants or families whose entities suffer from contemporary state violence, they make a study about the battles for the memories represented in national cinematographic productions (documentaries), built and released after the regime in the parents. Memory of paramount importance to discuss and reflect on as memories of these women: who had no front in the battles; who were disqualified / tortured / hated for being women and wishing to be in various spaces not allowed to them; women deprived of their rights; murdered women and their remains were hidden so that they were never found again; stories needed to be remembered and told for future stories. Historiographic debate necessary for the writing of women's history, particularly in the present political and social scenario, where sexist speeches and disqualifying women's struggles are urgent across the country. From the selected documents, we propose an analysis of the role of women. In the documentary “Memory for daily use”, you can listen carefully to women who share their personal struggles at the expense of a common theme. No film “In search of Iara”, based on the story of a militant woman, we will love several stories and memories of militants who fought in the resistance against a civil-military dictatorship. Memories that interrelate in the search for truth and justice.